MELHORIA NO LAYOUT E ENDEREÇAMENTO DO ESTOQUE DE CHAPAS DE AÇO EM UMA INDÚSTRIA DO SETOR AUTOMOTIVO : LAYOUT IMPROVEMENT AND STEEL PLATE STOCK ADDRESSING IN AN AUTOMOTIVE INDUSTRY - Leonel Luciano, Erik; Tsuguio Okano, Marcelo; Marcela dos Santos Almeida, Jennifer; Batista Ribeiro, Rosinei; Augusto Lemos de Santana, Wagner (Brazilian Journal of Production Engineering, 2020)
This paper aims to demonstrate how proper inventory addressing helps companies reduce costs, waste and unnecessary movement of their materials. As a specific objective, it focused on the creation of smart labels defining them by color with priority levels, seeking to adhere to the FIFO control of the month by the company’s logistics sector, as well as suggesting a change in inventory layout. The work had as main motivation the relevance of the theme with its practical content. The methodology used was the bibliographic research with the main theoretical thoughts and field study, analyzing the current form of storage and addressing of the advanced steel sheets and the company’s stock layout. As a final result, smart labels were created by level of importance, giving priority to addressing the highest turning plates. It was also suggested to implement both open and closed stock using cantilevers, leaving the leaner and more dynamic layout for the company, maximizing stock space, reducing waste of time in locating the item, eliminating unnecessary movements by the operator and to material losses.